Profil Dan Minat Mahasiswa Studi Di UIN Malang Sebagai Dasar Penentuan Strategi - Slamet, Slamet; Sucipto, Agus; Suprayitno, Eko (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
This research is to describe the student opinion on UIN Malang choice. In this qualitative and quantitative, to describe how student opinion about UIN Malang, who is student in UIN Malang, what department is student know and choice, and how to make marketing strategic to get the student. The finding showed that (1) the student in UIN Malang is more than 75% from East Java, (2) The student is more than 70%from MA (Madrasah Aliyah) (3) more than 60% the student have the aim to translate both Arabic and English. In marketing Strategic, (1) UIN Malang must come as the Market Leader, as UIN Malang has been a reputable university in Muslim society especially in MA in East Java, (2) UIN Malang must have marketing division to make public market not only in East Java, but in Indonesian.